RASIONALITAS INSTRUMENTAL DAN DOMINASI SISTEMIK DALAM MASYARAKAT DIGITAL: PERSPEKTIF NEO-MARXIS DAN TEORI KRITIS FRANKFURT TERHADAP PERKEMBANGAN KONSEPTUAL MASYARAKAT KONTEMPORER - Rahma Dona; Devina Novela; Aisyah Nur (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study examines how instrumental rationality contributes to the consolidation of systemic domination in the digital age, utilizing a Neo-Marxist and Frankfurt School Critical Theory framework. Instrumental rationality, which prioritizes efficiency and control, not only shapes bureaucratic and technological systems but also colonizes the social lifeworld through popular culture, algorithms, and digital communication. In this context, social media and the digital economy function as hegemonic tools that disseminate capitalist values symbolically and ideologically. Using Fairclough’s Critical Discourse Analysis, the research analyzes representative texts from media, public policies, and popular culture to reveal hidden mechanisms of domination within discursive practices and broader social structures. The findings show that systemic domination is no longer coercive but operates diffusely through technocratic logic, identity commodification, and the algorithmic structuring of everyday life. Habermas’s concept of communicative action offers a theoretical foundation for restoring deliberative public spaces and constructing a more participatory model of democracy. This study contributes to expanding the horizon of critical social theory by integrating digital, cultural, and ethical perspectives. It highlights the importance of media literacy, algorithmic justice, and cultural resistance as pathways toward holistic and transformative emancipation. Ultimately, it calls for a socially just, reflexive, and human-centered digital order.